Sekuritisasi Isu Human Traffickingdi Indonesia - Kamboja Pada Kasus Judi Daring - Muhammad Shandy Prasetyo; M Arsy Ash Shiddiqy (Sisi Lain Realita Another Side Of Reality Journal Criminology, 2026)
This study analyzes the securitization process of the human trafficking issue between Indonesia and Cambodia within the context of online gambling practices. This research employs constructivism, securitization theory, and the concept of cross-border crime. The method used is descriptive qualitative with in-depth interviews and documentation study. The findings reveal two main conclusions. First, online gambling practices are socially constructed by criminal syndicates as operational legitimacy shields, exploiting normative gaps in casino legality in Cambodia's border areas. Second, securitization occurs in a multi-level and cumulative manner: at Indonesia's domestic level, all three securitization stages have taken place comprehensively, while at the bilateral level, the process remains constrained by jurisdictional limitations and normative incoherence. This study concludes that securitizing transnational crime requires process coherence across all relevant states.